PCR screening of antimicrobial resistance genes in faecal samples from Australian and Chinese children - Ravensdale, J.; Xian, D.; Wei, C.; Lv, Q.; Wen, X.; Guo, J.; Coorey, Ranil; LeSouëf, P.; Lu, F.; Zhang, G.; Dykes, Gary (Elsevier, 2018)
Objectives: Recent public awareness campaigns on the risk of antibiotic resistance in pathogenic microbes has placed pressure on governments to enforce stricter antimicrobial stewardship policies on hospitals and the agricultural industry. In this study, faecal samples from Australian and Chinese children were screened for the presence of antimicrobial resistance genes (ARGs) in order to identify demographics at risk of carriage of these genes and to examine antimicrobial stewardship policies from the two countries that may influence carriage. Methods: Faecal samples from 46 Australian and 53 Chinese children were screened by PCR for the presence of six clinically relevant ARGs. Clinical and demographic data were also collected from each patient. Results: More than 90% of faecal samples from Chinese children tested positive for ß-lactam, macrolide, tetracycline and aminoglycoside resistance genes, which was substantially higher than Australian samples. Besides country of origin, no clear trend could be seen to predict carriage of ARGs. The exception to this was Chinese-born children who immigrated to Australia having higher rates of carriage of blaTEMand tetM genes than children born and still living in Australia. Conclusions: These data indicate that Chinese children are more likely to carry certain ARGs than Australian children. The Chinese government has recently implemented strict policies to control the overuse of antibiotics in hospitals. However, many of these policies do not extend to the agricultural industry, which could explain the differences seen in this study.